Kompetenzentwicklung in der Medizininformatik-Initiative (MII) – Lehrangebote für einen souveränen und sicheren Umgang mit medizinischen Daten - Knaup-Gregori, Petra; Boeker, Martin; Kirsten, Toralf; Krefting, Dagmar; Schiller, Erik; Schmücker, Paul; Schüttler, Christina; Seim, Anne; Spreckelsen, Cord; Winter, Alfred (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2024)
In order to achieve the goals of the Medical Informatics Initiative (MII), staff with skills in the field of medical informatics and data science are required. Each consortium has established training activities. Further, cross-consortium activities have emerged. This article describes the concepts, implemented programs, and experiences in the consortia. Fifty-one new professorships have been established and 10 new study programs have been created: 1 bachelorʼs degree and 6 consecutive and 3 part-time masterʼs degree programs. Further, learning and training opportunities can be used by all MII partners. Certification and recognition opportunities have been created. The educational offers are aimed at target groups with a background in computer science, medicine, nursing, bioinformatics, biology, natural science, and data science. Additional qualifications for physicians in computer science and computer scientists in medicine seem to be particularly important. They can lead to higher quality in software development and better support for treatment processes by application systems. Digital learning methods were important in all consortia. They offer flexibility for cross-location and interprofessional training. This enables learning at an individual pace and an exchange between professional groups. The success of the MII depends largely on society’s acceptance of the multiple use of medical data in both healthcare and research. The information required for this is provided by the MII’s public relations work. There is also an enormous need in society for medical and digital literacy.
CRIS-Team Scopus Importer:2024-05-24
Keywords: Digital literacy; Digital medicine; eLearning; Medical data science; Medical informatics